Autoimmune diseases and celiac disease which came first: genotype or gluten?. (2nd January 2016) - Diamanti, Antonella; Capriati, Teresa; Bizzarri, Carla; Ferretti, Francesca; Ancinelli, Monica; Romano, Francesca; Perilli, Alessia; Laureti, Francesca; Locatelli, Mattia
Abstract : Celiac disease (CD) is associated with several autoimmune diseases (ADs) and, in particular, thyroid autoimmunity (TA) and Type 1 diabetes (T1D). TA and T1D are defined as 'associated conditions' to CD (conditions at increased prevalence in CD but not directly related to gluten ingestion). The diagnosis of CD may precede or follow that of TA/T1D. To date, the available evidence suggests that the common genetic background is the main factor determining the high prevalence of the association. Conversely, no conclusive findings clarify whether extrinsic gluten-related factors (age at the first introduction, concomitant breastfeeding, length of gluten exposure and gluten-free diet) may link CD to the ADs. The aim of this review is to evaluate whether genetic background alone could explain the association between CD and ADs or if gluten-related factors ought to be considered. The pathophysiological links clarifying how the gluten-related factors could predispose to ADs will also be discussed.